Vocational High-School Teachers’ Perceptions of Media Used in EFL Classroom - Sri Atika Putri; Melvina Melvina; M Khairi Ikhsan (English Teaching and Linguistics Journal (ETLiJ), 2023)
Nowadays, in 21st-century learning, English teachers are demanded to be creative in teaching. Using media in teaching is one of the samples of teacher creativity. This study aims to determine the teachers’ perception of using media in teaching English at SMK N 1 Kinali. This type of research is descriptive research through a qualitative approach. In this study, the researcher used purposive sampling, involving three English teachers at SMK N 1 Kinali who used media during the teaching and learning process in the classroom. In collecting data, the researcher conducted observations and interviews with three teachers regarding what media the teacher used in learning English and how the teachers’ perception of using media in teaching English. The researcher found several media used in teaching English by teachers including; graphic media, audio media, project silent media, media games, and simulation. In addition, researchers also found that teachers have a positive perception of the use of media in teaching English. The teacher already has an understanding that the presence of media will support the smoothness of the teaching and learning process. However, teachers do not always use the media during the teaching and learning process. In terms of using the media, teachers also experience problems including a lack of internet access around the school environment and attacks on the media by students for matters not related to the teaching and learning process. However, behind that, all teachers are also trying to prepare media based on student characteristics which include different ways of learning, different interests in using media, and different levels of understanding.